English Teachers’ Conceptualizations of Key Competencies in English Language Teaching and Challenges to Their Implementation - Huashan Lu; Changgang Jiang; Fei Guo (Frontiers in Psychology, 2022)
Limited empirical research on the key competencies of front-line English teachers, particularly primary and middle school English teachers in rural regions, exists in the current literature. This research focuses on front-line instructors and examines their mastery of the key competencies in English language teaching. Through in-depth interviews, this paper examined eight rural junior middle school English teachers on their understanding of developing students’ key competencies in English language teaching, as well as the obstacles and challenges they experienced in curriculum implementation. The study found that although front-line teachers have a positive attitude toward the key competencies, there is still a certain gap between their comprehension of key competencies and policy requirements and practical demands. In order to implement core qualities and effectively promote curriculum reform, we need to strengthen teacher development training for front-line English teachers, especially for primary and secondary school English teachers in rural areas, to improve their understanding and professionalization of the new round of curriculum reform.